Rubber composite material, preparation method thereof and obtained tire

By using carbon separation method white carbon black as a reinforcement in tire rubber composite materials, the problems of traditional acid precipitation method white carbon black in vulcanization delay, poor reinforcement effect and environmental pollution are solved, and the goals of improving the performance and sustainable development of rubber composite materials are achieved.

CN119708656AActive Publication Date: 2025-03-28QINGDAO DOUBLESTAR TIRE IND CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411965134.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-03-28
Estimated Expiration
2044-12-30

AI Technical Summary

Technical Problem

The traditional acid precipitation method of white carbon black has problems such as vulcanization delay, relatively small specific surface area and structural degree, and poor reinforcement effect in tire rubber composite materials. At the same time, sulfuric acid leakage during its production process also leads to environmental pollution.

Method used

The carbon separation method of white carbon black is used as a reinforcement agent. The reasonable ratio of white carbon black to natural rubber, carbon black, vulcanizing agent and vulcanization accelerator is used to improve the vulcanization speed and mechanical properties of rubber composite materials, and the reasonable processing method is used to make it better disperse in the rubber composite materials.

Benefits of technology

It significantly improves the vulcanization characteristics, tear strength and aging performance of rubber composite materials, improves the production efficiency, driving safety and service life of tires, and achieves the goals of carbon emission reduction and sustainable development.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention provides a rubber composite material, a preparation method thereof and an obtained tire, and belongs to the technical field of tire rubber materials. According to the rubber composite material provided by the invention, the carbon-precipitation-method white carbon black is adopted as a reinforcing agent, so that the vulcanization characteristic Tc90 of the obtained rubber composite material can reach 14.82 min, the MH can reach 31.28 dNm, the tear strength of vulcanized rubber can reach 68.15 kN / m, the tear strength after aging can reach 31.86 kN / m, and the vulcanization, mechanical and aging properties of the rubber composite material are obviously superior to those of a traditional acid-precipitation-method white carbon black reinforced rubber composite material; the production efficiency, the driving safety and the service life of the tire are effectively improved. Besides, the carbon separation method white carbon black used in the rubber composite material is a chemical for recycling and reusing carbon dioxide, reasonable utilization of the carbon separation method white carbon black in the rubber composite material plays a positive role in promoting sustainable development of modern industry and achieving peak carbon neutralization, and meanwhile the environmental pollution problems such as leakage of sulfuric acid prepared through a traditional acid precipitation method are avoided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of tire rubber materials, and in particular relates to a rubber composite material, a preparation method thereof and a tire obtained therefrom. Background Art

[0002] As a reinforcing filler, white carbon black is widely used in the tire rubber industry. It has the advantages of good chemical stability, high temperature resistance, porosity, and large specific surface area. It can significantly improve the mechanical, heat generation, and anti-slip properties of tire rubber materials when used for tire rubber reinforcement. At present, the white carbon black used in tire rubber composite materials is mostly acid-precipitated white carbon black, which has a large number of silanol groups on the surface and an acidic pH. This will reduce the vulcanization rate of the rubber to a certain extent and increase the cost of tire production. In addition, ordinary acid-precipitated white carbon black also has the disadvantages of large particle size, relatively small specific surface area and structure, which will weaken the reinforcing effect of white carbon black to a certain extent.

[0003] As a byproduct of industrial production, CO2 emissions will reach 36.8 billion tons globally in 2023, showing a continued upward trend compared to 2022. Carbon emission reduction and the rational recycling of carbon dioxide have become key links in current ecological environmental protection and sustainable development. If the carbon dioxide recycling products can be used in the production of radial tire formulas, it will play a positive role in promoting the sustainable development of modern industry and achieving carbon peak and carbon neutrality. Summary of the invention

[0004] The present invention provides a rubber composite material, a preparation method thereof and the resulting tire. The rubber composite material uses carbon-precipitated silica as a reinforcing agent, overcoming the problems of delayed vulcanization, relatively small specific surface area and structure, and poor performance of reinforced rubber materials of traditional acid precipitation silica rubber materials, and plays a positive role in promoting the sustainable development of modern industry and accelerating carbon peak and carbon neutrality.

[0005] In order to achieve the above-mentioned object, the present invention provides a rubber composite material, in which carbon-separated white carbon black is used as a reinforcing agent. The obtained rubber composite material is subjected to a vulcanization test at 151° C. for 40 min, and its vulcanization characteristics Tc90 reaches 14.82 min, MH reaches 31.28 dNm, the tear strength of the vulcanized rubber reaches 68.15 kN / m, and the tear strength after aging reaches 31.86 kN / m.

[0006] Preferably, the rubber composite material further comprises natural rubber, carbon black, a vulcanizing agent and a vulcanization accelerator, and the mass ratio of carbon separation white carbon black to natural rubber, carbon black, a vulcanizing agent and a vulcanization accelerator is 2-2.2: 20-22: 8.8-9: 1-1.1: 0.18-0.2. It is understandable that the scheme limits the addition ratio of each component, and if any component in the above ratio is added in too much or too little amount, the processing performance of the rubber composite material will deteriorate, and the vulcanization speed, Mooney viscosity, hardness will be too high or too low, and other problems will be caused, thereby affecting the mechanical and other related properties of the rubber composite material.

[0007] Preferably, the carbon black is carbon black N375, with a BET value of 103m 2 / g; the vulcanizing agent is insoluble sulfur HD-OT20-A grade; the vulcanization accelerator is vulcanization accelerator NS.

[0008] Preferably, the rubber composite material further comprises an active agent, an adhesive and an antioxidant, and the mass ratio of carbon separation white carbon black to the active agent, the adhesive and the antioxidant is 2-2.2:1.5-1.7:1.4-1.6:0.4-0.41. It is understandable that the scheme limits the addition ratio of each component, and if any component in the above ratio is added in too much or too little amount, the processing performance of the rubber composite material will deteriorate, the vulcanization speed, Mooney viscosity, hardness will be too high or too low, and other problems will affect the mechanical and other related properties of the rubber composite material.

[0009] Preferably, the active agent is indirect zinc oxide;

[0010] The adhesive is a mixture of resorcinol formaldehyde resin, cobalt decanoate and adhesive RA;

[0011] The antioxidant is a mixture of antioxidant 4020 and antioxidant RD.

[0012] Preferably, the mass ratio of the resorcinol formaldehyde resin, cobalt decanoate and adhesive RA in the adhesive is 1:0.7-0.8:3.2-3.4;

[0013] The mass ratio of antioxidant 4020 to antioxidant RD in the antioxidant is 1:0.3-0.4.

[0014] As a preferred method, the pH of carbon separation white carbon black is 7.2, and the BET is 224.4m 2 / g, DBP absorption value is 2.64cm 3 / g; using it in rubber composite materials, compared with acid-precipitated silica, it can increase the vulcanization speed of rubber composite materials, and Tc90 reaches 14.82min.

[0015] It is understandable that compared with traditional acid-precipitated silica, carbon-separated silica has a larger specific surface area and structure. When used to reinforce rubber composites, it can make them have better tear strength and aging properties, and can effectively improve the vulcanization rate of rubber composites, the mechanical properties of vulcanized rubber and aging properties. Carbon-separated silica is also a carbon dioxide recovery and reuse chemical. Its rational use in rubber composites has a positive effect on promoting the sustainable development of modern industry and achieving carbon peak and carbon neutrality. Carbon-separated silica is used in rubber composites. Compared with traditional acid-precipitated silica, it can provide the required alkaline catalytic conditions for the vulcanization reaction of sulfur atoms and rubber molecular chains, thereby improving the vulcanization rate of rubber. The acidic environment provided by the acidic surface of acid-precipitated silica will have the opposite effect, that is, delaying vulcanization. Compared with traditional acid-precipitated silica, carbon-separated silica has a larger specific surface area and structure. When reinforcing rubber composites, proper processing can better disperse it in the composite and improve the mechanical properties of rubber composites such as tear strength. The high chemical stability, high temperature resistance and chemical bonds with rubber that are more stable than physical hydrogen bonds of white carbon black, coupled with the good dispersion of carbon-separated white carbon black in the rubber matrix, give the rubber composite better thermal oxidative aging properties.

[0016] The present invention also provides a method for preparing the rubber composite material according to any one of the above technical solutions, comprising the following steps:

[0017] Place carbon separation white carbon black, natural rubber, carbon black, activator, adhesive and antioxidant in an internal mixer, mix at 140-160°C for 2-4 minutes, and after mixing evenly, discharge the rubber and press into sheets to obtain a masterbatch;

[0018] The obtained masterbatch, vulcanizing agent, vulcanization accelerator and adhesive are placed in an internal mixer, mixed evenly, and then discharged and sheeted to obtain the final mixed rubber;

[0019] The final rubber mixture was placed in a vulcanizer and vulcanized at 151° C. for 30 min to obtain a rubber composite material.

[0020] Preferably, the vulcanization characteristics Tc90 of the obtained rubber composite material reaches 14.82 min, MH reaches 31.28 dNm, the tear strength of the vulcanized rubber reaches 68.15 kN / m, and the tear strength after aging reaches 31.86 kN / m.

[0021] The present invention also provides a tire, which is prepared from the rubber composite material described in any one of the above technical solutions.

[0022] Compared with the prior art, the advantages and positive effects of the present invention are:

[0023] 1. The rubber composite material provided by the present invention uses carbon-precipitated silica as a reinforcing agent, so that the vulcanization characteristics Tc90 of the obtained rubber composite material can reach 14.82min, MH reaches 31.28dNm, the tear strength of the vulcanized rubber reaches 68.15kN / m, and the tear strength after aging reaches 31.86kN / m, which are significantly better than the vulcanization, mechanical and aging properties of the traditional acid-precipitated silica reinforced rubber composite material, and effectively improve the production efficiency, driving safety and service life of the tire.

[0024] 2. The carbon separation method silica used in the rubber composite material provided by the present invention is a carbon dioxide recovery and reuse chemical. Its rational use in rubber composite materials plays a positive role in promoting the sustainable development of modern industry and achieving carbon peak and carbon neutrality, while avoiding environmental pollution problems such as leakage of sulfuric acid prepared by traditional acid precipitation method. DETAILED DESCRIPTION

[0025] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0026] Example 1

[0027] Preparation of carbon separation silica rubber composite materials:

[0028] 2.2 parts of carbon-based white carbon black, 21 parts of natural rubber, 8.8 parts of carbon black N375, 1.6 parts of indirect zinc oxide, 0.3 parts of resorcinol formaldehyde adhesive resin, 0.24 parts of cobalt decanoate, 0.3 parts of antioxidant 4020 and 0.1 parts of antioxidant RD were placed in an internal mixer and mixed at 150° C. for 3 minutes. After mixing evenly, the mixture was discharged and sheeted to obtain a masterbatch;

[0029] The obtained masterbatch, 1 part of insoluble sulfur OT20, 0.19 part of vulcanization accelerator NS and 1 part of adhesive RA are placed in an internal mixer, mixed evenly, discharged and sheeted to obtain the final rubber mix;

[0030] The final rubber mixture was placed in a vulcanizer and vulcanized at 151° C. for 30 min to obtain a carbon-fractionated silica rubber composite material.

[0031] The performance of the carbon-fractionated silica rubber composite material prepared in this example was tested, and the testing standards for the vulcanization properties Tc90 and MH of the mixed rubber and the tear strength and hot air aging of the vulcanized rubber were referred to GB / T 16584-1996, GB / T529-2008, and GB / T 3512-2001, respectively.

[0032] The results show that the mixed rubber of the carbon-precipitated silica rubber composite material prepared in this embodiment has a vulcanization characteristic Tc90 of 14.82 min, MH of 31.28 dNm, vulcanized rubber tear strength of 68.15 kN / m, and tear strength of 31.86 kN / m after aging, which is significantly better than the performance of the rubber composite material prepared by conventional ordinary acid precipitation silica (i.e., the following comparative example 1), and effectively improves the production efficiency, driving safety and service life of the tire.

[0033] Example 2

[0034] Preparation of carbon separation silica rubber composite materials:

[0035] 2 parts of carbon-based white carbon black, 22 parts of natural rubber, 9 parts of carbon black N375, 1.7 parts of indirect zinc oxide, 0.32 parts of resorcinol formaldehyde adhesive resin, 0.25 parts of cobalt decanoate, 0.3 parts of antioxidant 4020 and 0.11 parts of antioxidant RD were placed in an internal mixer and mixed at 150° C. for 3 minutes. After mixing evenly, the mixture was discharged and sheeted to obtain a masterbatch;

[0036] The obtained masterbatch, 1.1 parts of insoluble sulfur OT20, 0.2 parts of vulcanization accelerator NS and 1.03 parts of adhesive RA were placed in an internal mixer, mixed evenly, discharged and sheeted to obtain the final rubber mix;

[0037] The final rubber mixture was placed in a vulcanizer and vulcanized at 151° C. for 30 min to obtain a carbon-fractionated silica rubber composite material.

[0038] The performance of the carbon-fractionated silica rubber composite material prepared in this example was tested, and the testing standards for the vulcanization properties Tc90 and MH of the mixed rubber and the tear strength and hot air aging of the vulcanized rubber were referred to GB / T 16584-1996, GB / T529-2008, and GB / T 3512-2001, respectively.

[0039] The results show that the mixed rubber of the carbon-precipitated silica rubber composite material prepared in this embodiment has a vulcanization characteristic Tc90 of 14.52 min, MH of 31.05 dNm, vulcanized rubber tear strength of 66.87 kN / m, and tear strength of 30.74 kN / m after aging, which are significantly better than the performance of the rubber composite material prepared by the conventional ordinary acid precipitation silica, and effectively improve the production efficiency, driving safety and service life of the tire.

[0040] Example 3

[0041] Preparation of carbon separation silica rubber composite materials:

[0042] 2 parts of carbon-based white carbon black, 20 parts of natural rubber, 8.8 parts of carbon black N375, 1.5 parts of indirect zinc oxide, 0.3 parts of resorcinol formaldehyde adhesive resin, 0.22 parts of cobalt decanoate, 0.3 parts of antioxidant 4020 and 0.1 parts of antioxidant RD were placed in an internal mixer and mixed at 150° C. for 3 minutes. After mixing evenly, the mixture was discharged and sheeted to obtain a masterbatch;

[0043] The obtained masterbatch, 1 part of insoluble sulfur OT20, 0.19 part of vulcanization accelerator NS and 0.95 part of adhesive RA are placed in an internal mixer, mixed evenly, discharged and sheeted to obtain the final rubber mix;

[0044] The final rubber mixture was placed in a vulcanizer and vulcanized at 151° C. for 30 min to obtain a carbon-fractionated silica rubber composite material.

[0045] The performance of the carbon-fractionated silica rubber composite material prepared in this example was tested, and the testing standards for the vulcanization properties Tc90 and MH of the mixed rubber and the tear strength and hot air aging of the vulcanized rubber were referred to GB / T 16584-1996, GB / T529-2008, and GB / T 3512-2001, respectively.

[0046] The results show that the mixed rubber of the carbon-precipitated silica rubber composite material prepared in this embodiment has a vulcanization property Tc90 of 14.98 min, MH of 31.86 dNm, vulcanized rubber tear strength of 69.84 kN / m, and tear strength of 33.59 kN / m after aging, which are significantly better than the performance of the rubber composite material prepared by the conventional ordinary acid precipitation silica, and effectively improve the production efficiency, driving safety and service life of the tire.

[0047] Comparative Example 1

[0048] The same as Example 1, except that in the step of preparing the rubber composite material, no carbon separation silica was added, but 2.2 parts of conventional acid precipitation silica were used instead.

[0049] The test standard is the same as that of Example 1. The results show that the mixed rubber of the rubber composite material prepared in Comparative Example 1 has a vulcanization test of 40 minutes at 151°C, and the vulcanization characteristics Tc90 reaches 15.74min, MH reaches 29.05dNm, the tear strength of the vulcanized rubber reaches 63.76kN / m, and the tear strength after aging reaches 28.21kN / m. Compared with the rubber composite material added with carbon fractionation white carbon black, the vulcanization speed, MH, tear strength of the vulcanized rubber and aging performance of the rubber composite material added with conventional ordinary acid precipitation white carbon black are significantly reduced. This is because the surface of carbon fractionation white carbon black can provide the required alkaline catalytic conditions for the vulcanization reaction of sulfur atoms and rubber molecular chains, thereby improving the vulcanization speed of the rubber, while the acidic environment provided by conventional ordinary acid precipitation white carbon black will play the opposite role, that is, delay vulcanization. Compared with traditional acid precipitation silica, carbon separation silica has a larger specific surface area and structure. When reinforcing rubber composite materials, proper processing can better disperse it in the composite material, improving the crosslinking density, tear strength and other mechanical properties of the rubber composite. The high chemical stability, high temperature resistance and chemical bonds with rubber that are more stable than physical hydrogen bonds, as well as the good dispersion of carbon separation silica in the rubber matrix give the rubber composite better thermal oxidation aging performance.

[0050] Comparative Example 2

[0051] The same as Example 1, except that in the step of preparing the rubber composite material, the amount of carbon-free white carbon black added is changed from 2.2 parts to 1.8 parts.

[0052] The test standard is the same as that of Example 1. The results show that the mixed rubber of the rubber composite material prepared in Comparative Example 1 is vulcanized at 151°C for 40 minutes, and the vulcanization characteristics Tc90 reaches 13.84min, MH reaches 28.68dNm, the tear strength of the vulcanized rubber reaches 60.64kN / m, and the tear strength after aging reaches 27.52kN / m. Compared with the rubber composite material with 2.2 parts of carbon-fractionated silica added, the vulcanization speed of the rubber composite material with 1.8 parts of carbon-fractionated silica added is slightly accelerated, but the vulcanization characteristics MH, the tear strength of the vulcanized rubber and the aging performance are significantly reduced. This is because the carbon-fractionated silica dispersed in the unit volume is reduced, and the reinforcement effect is reduced accordingly. At the same time, due to the high chemical stability, high temperature resistant chemical properties of silica, and the chemical bonds formed with rubber that are more stable than physical hydrogen bonds, the reduction of carbon-fractionated silica dispersed in the unit volume will also reduce the thermal oxidation aging performance of the rubber composite.

[0053] Comparative Example 3

[0054] The same as Example 1, except that in the step of preparing the rubber composite material, the amount of carbon-free white carbon black added is changed from 2.2 parts to 2.5 parts.

[0055] The test standard is the same as that of Example 1. The results show that the mixed rubber of the rubber composite material prepared in Comparative Example 1 is vulcanized at 151°C for 40 minutes, and the vulcanization characteristics Tc90 reaches 15.22min, MH reaches 30.28dNm, the tear strength of the vulcanized rubber reaches 64.28kN / m, and the tear strength after aging reaches 29.14kN / m. Compared with the rubber composite material added with 2.2 parts of carbon-fractionated silica, the vulcanization speed, MH, tear strength of the vulcanized rubber and aging performance of the rubber composite material added with 2.5 parts of carbon-fractionated silica are all reduced to a certain extent. This is because excessive carbon-fractionated silica is not conducive to processing and dispersion, and its dispersibility deteriorates, which leads to a decrease in its crosslinking, tear strength and aging performance. Among them, the increase in the number of fillings will also affect the vulcanization time to a certain extent.

Claims

1. A rubber composite material, characterized in that: The rubber composite material uses carbon-fractionated silica as a reinforcing agent. The obtained rubber composite material is subjected to a vulcanization test at 151° C. for 40 minutes, and its vulcanization characteristics Tc90 reaches 14.82 minutes, MH reaches 31.28 dNm, the tear strength of the vulcanized rubber reaches 68.15 kN / m, and the tear strength after aging reaches 31.86 kN / m.

2. The rubber composite material according to claim 1, characterized in that: The rubber composite material also includes natural rubber, carbon black, a vulcanizing agent and a vulcanization accelerator. The mass ratio of carbon separation white carbon black to natural rubber, carbon black, a vulcanizing agent and a vulcanization accelerator is 2-2.2:20-22:8.8-9:1-1.1:0.18-0.

2.

3. The rubber composite material according to claim 2, characterized in that: The carbon black is carbon black N375, and the BET is 103m 2 / g; the vulcanizing agent is insoluble sulfur HD-OT20-A grade; the vulcanization accelerator is vulcanization accelerator NS.

4. The rubber composite material according to claim 2 or 3, characterized in that: The rubber composite material also includes an active agent, an adhesive and an antioxidant, and the mass ratio of carbon-separated white carbon black to the active agent, the adhesive and the antioxidant is 2-2.2:1.5-1.7:1.4-1.6:0.4-0.

41.

5. The rubber composite material according to claim 4, characterized in that: The active agent is indirect zinc oxide; The adhesive is a mixture of resorcinol formaldehyde resin, cobalt decanoate and adhesive RA; The antioxidant is a mixture of antioxidant 4020 and antioxidant RD.

6. The rubber composite material according to claim 5, characterized in that: The mass ratio of the adhesive resorcinol formaldehyde resin, cobalt decanoate and adhesive RA is 1:0.7-0.8:3.2-3.4; The mass ratio of antioxidant 4020 to antioxidant RD in the antioxidant is 1:0.3-0.

4.

7. The rubber composite material according to any one of claims 1 to 6, characterized in that: Carbon fraction white carbon black pH is 7.2, BET is 224.4m 2 / g, DBP absorption value is 2.64cm 3 / g; When used in rubber composites, it can increase the vulcanization speed of rubber composite materials compared to acid-precipitated silica, with Tc90 reaching 14.82min.

8. The method for preparing the rubber composite material according to any one of claims 4 to 7, characterized in that: The following steps are involved: Place carbon separation white carbon black, natural rubber, carbon black, active agent, adhesive and antioxidant in an internal mixer, mix at 140-160°C for 2-4 minutes, and after mixing evenly, discharge the rubber and press into sheets to obtain a masterbatch; The obtained masterbatch, vulcanizing agent, vulcanization accelerator and adhesive are placed in an internal mixer, mixed evenly, and then discharged and sheeted to obtain the final mixed rubber; The final rubber mixture was placed in a vulcanizer and vulcanized at 151° C. for 30 min to obtain a rubber composite material.

9. The preparation method according to claim 8, characterized in that: The vulcanization properties of the obtained rubber composite material Tc90 reached 14.82min, MH reached 31.28dNm, the tear strength of the vulcanized rubber reached 68.15kN / m, and the tear strength after aging reached 31.86kN / m.

10. A tire, characterized in that The tire is prepared from the rubber composite material according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Preparation method of high-quality white carbon black for rubber

    CN101704525A

  • Rubber composition for tread of truck radial tire with low hysteresis loss

    CN104119578A

  • Composite material, sizing material and tire

    CN107759849A

  • Rubber Composition of Tire Subtread and Tire Manufactured by Using The Same

    KR102117031B1

  • Low-roller-resistance energy-saving rubber conveying belt and covering rubber thereof

    WO2022127312A1